Scientific and Theoretical Model of Continuous Inclusive Education for Equity and Quality Learning to support Sustainable Development Goals (SDGs) - Sanobar Yuldashevna Ashurova; Nargiza Jabborqizi Eshbekova; Khidirov Ural Dobilovich; Odilbek Ulugbekugli Askaraliev; Akbar Namozovich Rasulov; Dilnura Abdurashidovna Sultonova; Munisa Dustnazar Omonova (ASEAN Journal of Educational Research and Technology, 2026)
This study explores the scientific and theoretical foundations of continuous inclusive education to promote equitable and high-quality learning. The research applies mixed-methods analysis, combining literature review and case studies to identify barriers and strategies in inclusive education. Findings indicate that while legislative reforms have advanced inclusion, challenges persist in teacher preparedness, infrastructure, and social attitudes. These results are significant because they reveal that sustainable inclusion requires alignment between educational policies and community awareness. The study highlights the importance of international collaboration and adaptive pedagogical frameworks such as Universal Design for Learning and Universal Design for Instruction. By addressing these factors, inclusive education can effectively contribute to achieving Sustainable Development Goals 4 and 10 by ensuring equal access, reducing inequality, and strengthening the professional capacity of teachers to create supportive learning environments.